Fraude a los acreedores: la acción pauliana o revocatoria y la acción oblicua o subrogatoria - Franciskovic Ingunza, Beatriz (2021)
By means of this comment, the legal figure, misnamed, by our civil legal system, as the fraud of the legal act it´s analyzed, since obviously there is no fraud or deception of the legal act itself, but what really happens, it is a direct deception, cunning or malicious act on the part of the debtor directed directly at the creditor. Fraud to creditors occurs as long as there is a mandatory link between two subjects. It consists of the improper conduct or behavior of the debtor towards his creditor, who in order not to comply with his credit diminishes his assets either onerously or gratuitously and, or omits to collect a debt he has with another debtor in another mandatory legal relationship. Faced with this situation, the legal system grants, among other actions to the creditor: The Paulian or revocation action and the oblique or sub-rogatory action.